Investigating the Roles of the Four Sources of Self-Efficacy Beliefs in an EFL Listening Context - Kim, Hyang-Il (Theory and Practice of Second Language Acquisition, 2022)
Research in the academic context has revealed the positive roles of self-efficacy in teaching and learning, showing that a thorough understanding of self-efficacy is essential. In this study, the relationships between the four principal sources and the formation of self-efficacy belief proposed by Bandura (1997) are examined in order to further this understanding. Based on this, several empirical studies have attempted to explore these relationships in various fields, but the relevant research appears to have produced insufficient empirical data in the field of language learning to support the theory. Therefore, this study aims to investigate how these sources affect basic self-efficacy (BSSE) and advanced skill self-efficacy (ASSE) classified according to the difficulty of listening tasks in English. As many as 107 Korean university students participated in the study and mediation analysis was employed to examine the relationships. The results show that all four sources act as mediators of BSSE, and all but physiological and emotional states serve as mediators of ASSE. The findings support Bandura’s hypothesis and the pedagogical implications are discussed.